Kearifan Lokal Sebagai Motivasi Dalam Meningkatkan Kinerja Lembaga Perkreditan Desa Sibetan - I Kadek Dwi Agus Wedantara; I Nyoman Rasmen Adi (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe success of the LPD of the concept and establishment and management of the LPD which is extracted from the local and cultural wisdom of the Balinese people who are based on togetherness, kinship and mutual cooperation. The idea of the LPD is rooted in the customs and culture of the Balinese people. The cause of the LPD's success also comes from the pattern of community-based management based on family values and mutual cooperation in the framework of Balinese customs and culture. The community in Desa Pakraman is the owner and manager of the LPD who performs tasks and functions in the bond of commitment to prosperity and mutual progress. With a variety of local wisdom services provided by the LPD to its customers, making these services felt comfortable and not rigid in regulations as applied in banking. As a result of the comfort and trust given by customers to the LPD Sibetan, LPD performance has increased along with customer trust. Besides that, the number of assets owned by the LPD has increased.